Effects of Riociguat and Sildenafil in a murine model of chronic right ventricular pressure overload - Schymura, Yves; Justus Liebig University Giessen (My University, 2012)
Right heart failure is a prevalent mechanism of cardiovascular collapse and dis-tinctly different from left heart failure. Conventionally, afterload reduction has beenthe main focus to treat right ventricular (RV) dysfunction, but it cannot be achievedin many cases. A new strategy is to directly target RV remodelling. Pulmonaryartery banding (PAB) in mice is used to induce a chronic pressure overload on theRV, without any changes in the pulmonary vasculature.This work addressed two questions: a) the time-course of effects of PAB onright- and left-ventricular (LV) hypertrophy and function, assessed non-invasivelyvia magnetic resonance imaging (MRI). b) Stimulation of the nitric oxide pathwaywas shown to ameliorate maladaptive changes in murine models of chronic LV pres-sure overload. Therefore, the effects of the sGC stimulator Riociguat and the PDE5inhibitor Sildenafil on RV function and fibrosis were investigated.Chronic RV pressure overload was induced by PAB in male C57Bl/6 wild-typemice. For the time-course study, 1, 3, 7, 14, 28, 56 and 105 days after PAB, thefunctional and morphological consequences of sustained pressure overload on the RVand LV were assessed non-invasively using MRI. Additionally, the time-course of theeffects of PAB on cardiomyocyte size and fibrosis was investigated.For the pharmacological intervention study, drug treatment was started sevendays after surgery for 2 weeks. Animals received either 30 mg/kg/d Riociguat peros, Sildenafil 100 mg/kg/d per drinking water, or placebo. The consequences ofthe sustained pressure overload on RV fibrosis, cardiomyocyte size and functionwere assessed using Picrosirius red staining, WGA-FITC staining and MagneticResonance Imaging.PAB led to RV dilatation, indicated by an increase in end-diastolic volume. RVmass, cardiomyocyte size, as well as the collagen content of the RV increased inbanded animals. The ejection fraction and the stroke volume (SV) of the RV de-creased, as well as the LV SV and the cardiac output (CO).Whilst RV mass increasedcontinually over the time-course of the study, the RV performance declined initially,followed by a weak compensatory phase. In the course of the study, the heart con-tinued to decompensate, which finally resulted in heart failure of the animals.Treatment with both Riociguat and Sildenafil led to significant improvementsin RV ejection fraction (35.4 ± 1.7% vs. 43.7 ± 2.2% vs. 48.2 ± 3.3% [Placebovs. Riociguat vs. Sildenafil]), but only Riociguat significantly reduced the collagencontent of the RV (5.6 ± 0.3% vs. 3.0 ± 0.8% vs. 5.4 ± 0.2%). Neither drug had ef-fects on RV hypertrophy (62.3 ± 3.1 mg vs. 59.6 ± 2.5 mg vs. 57.1 ± 2.2 mg), on theRV/(LV+S) ratio (0.84 ± 0.04 mg/mg vs. 0.91 ± 0.04 mg/mg vs. 0.83 ± 0.03 mg/mg),nor on cardiomyocyte size (20.7 ± 0.6 μm vs. 19.8 ± 0.3 μm vs. 19.7 ± 0.6 μm).It was shown, that chronic pressure overload in C57Bl/6 mice induced RV di-latation, hypertrophy and contractile dysfunction. Furthermore, LV performancewas negatively affected by intraventricular interaction, resulting in decreased LVSV and CO. Riociguat and Sildenafil both led to significant improvements in RVfunction, without any changes in RV mass or cardiomyocyte size. One reason forthe functional improvement of the RV under Riociguat treatment is the decreasein collagen content, making the RV more apt to deal with the pressure overload.Further experiments will be needed to determine the mechanism of the functionalimprovement with Sildenafil treatment, and the reason for the differential effects of the drugs.

Rechtsherzversagen ist ein vorherrschender Mechanismus des kardiovaskulären Kol-lapses und unterscheidet sich deutlich vom Linksherzversagen. Die konventionelleMethode, um rechtsventrikuläre (RV) Dysfunktion zu behandeln, ist eine Redukti-on der Nachlast. Dies ist jedoch in vielen Fällen nicht möglich. Eine neue Strategiestellt die Behandlung der RV Hypertrophie dar. Pulmonal-arterielles Banding (PAB)in Mäusen wird verwendet, um RV Hypertrophie auszulösen, ohne eine Veränderungdes pulmonalen Gefäßsystems zu induzieren.In dieser Arbeit wurden zwei Fragestellungen behandelt: a) der zeitliche Ver-lauf der Effekte des PAB auf die rechts- und linksventrikuläre (LV) Hypertrophieund Funktion mittels Magnetresonanztomographie (MRT) zu untersuchen. b) Eswurde gezeigt, dass der Stickstoffmonoxid (NO)-Signalweg an der Entwicklung derLV Hypertrophie entscheidend beteiligt ist. Daher wurden die Effekte des löslichenGuanylatzyklase-Stimulators (sGC-Stimulator) Riociguat, sowie des Phosphodies-terase 5-Hemmers Sildenafil, auf die RV Hypertrophie und Funktion untersucht.Bei C57Bl6-Mäusen wurde eine chronische Druckbelastung für den rechten Ven-trikel durch eine PAB-Operation erzeugt. Für die Langzeitstudie wurden die Folgender anhaltenden Drucküberlastung auf RV und LV Morphologie und Funktion 1, 3, 7,14, 28, 56 und 105 Tage nach der PAB-Operation nicht-invasiv mit MRT untersucht.Zusätzlich wurden der zeitliche Verlauf der Effekte des PAB auf die Kardiomozy-tengröße, sowie den Grad der Fibrosierung untersucht.In der pharmakologischen Interventionsstudie, wurde die Behandlung mit Rioci-guat (30 mg/kg/d p.o.), resp. Sildenafil (100 mg/kg/d p.o.), 7 Tage nach der Ope-ration für eine Dauer von 14 Tagen durchgeführt. Nach 21 Tagen wurden die Aus-wirkungen einer dauerhaften Druckbelastung auf die RV Morphologie und Funktionunter Verwendung von Magnetresonanztomographie untersucht. Desweiteren wurdeder Grad der Fibrosierung, sowie die Kardiomyozytengröße durch eine histologischeUntersuchung analysiert.PAB-operierte Mäuse zeigten etliche Merkmale der RV Dysfunktion. PAB führtezu RV Dilatation verglichen mit Sham-operierten Tieren, gemessen als eine Zunahmedes end-diastolischen Volumens. Sowohl RV Masse als auch Kardiomyozytengrößeund Fibrosierungsgrad nahmen in PAB-Mäusen zu. Die Ejektionsfraktion (EF) unddas Schlagvolumen (SV) des RV nahmen ab. Das LV-SV und das Herzzeitvolumennahmen ab. Während die RV Masse über den Versuchszeitraum zunahm, fiel die RVLeistung initial stark ab, woraufhin eine zunächst kompensatorische Phase folgte.Mit Fortschritt der Studie dekompensierte das Herz zusehends, was schlussendlichim Herzversagen der Tiere mündete.Sowohl die Behandlung der Tiere mit Riociguat, als auch mit Sildenafil, führ-te zu signifikanten Verbesserungen der RV EF (35.4 ± 1.7% vs. 43.7 ± 2.2% vs.48.2 ± 3.3% [Placebo vs. Riociguat vs. Sildenafil]), aber nur Riociguat reduzierte si-gnifikant den Fibrosierungsgrad des RV (5.6 ± 0.3% vs. 3.0 ± 0.8% vs. 5.4 ± 0.2%).Weder Riociguat, noch Sildenafil, hatten einen Effekt auf die RV Hypertrophie(62.3 ± 3.1 mg vs. 59.6 ± 2.5 mg vs. 57.1 ± 2.2 mg), auf den RV/(LV+S) Quotien-ten (0.84 ± 0.04 mg/mg vs. 0.91 ± 0.04 mg/mg vs. 0.83 ± 0.03 mg/mg), oder auf dieKardiomyozytengröße (20.7 ± 0.6 μm vs. 19.8 ± 0.3 μm vs. 19.7 ± 0.6 μm).Es wurde gezeigt, dass die chronische Drucküberlastung in C57Bl/6 Wildtyp-Mäusen zu RV Dilatation, Hypertrophie und kontraktiler Dysfunktion führt. Zu-sätzlich wurde die LV Leistung durch interventrikuläre Interaktion, d. h. durch eineReduktion des LV Schlagvolumens und des Herzzeitvolumens, beeinträchtigt. SowohlRiociguat als auch Sildenafil führten zu signifikanter Verbesserung der RV Funkti-on, ohne Veränderungen in der RV Masse oder Kardiomyozytengröße ausgelöst zuhaben. Ein Grund für die funktionelle Verbesserung unter Riociguat-Behandlungkönnte die Reduktion der RV Fibrosierung sein.Weitere Studien sollten durchgeführtwerden, um den Mechanismus der funktionellen Verbesserung unter Sildenafil-Gabe,sowie die unterschiedlichen Effekte der Substanzen zu untersuchen.
Effekte von Riociguat und Sildenafil in einem murinen Modell der chronischen rechtsventrikulären Drucküberlast
Keywords: NO; Herz; Hypertrophie; sGC; PDE; NO; Heart; Hypertrophy; sGC; PDE; ddc:610